Гуманістична спрямованість інноваційних процесів у соціальній педагогіці - Дурманенко, Євгенія Аристархівна; Панченко, Вікторія Валеріївна; Durmanenko, Yevheniia A.; Panchenko, Viktoriia V. (Східноєвропейський національний університет імені Лесі Українки, 2014)
На сучасному етапі розвитку українського суспільства актуальним є дослідження інноваційних процесів у соціально-педагогічній роботі, визначення закономірностей і принципів соціальної педагогіки. Розкрито сутність понять «інновація», «інноваційний процес»; проаналізовано закономірності та принципи соціально- педагогічної роботи; визначено типи нововведень у соціальній педагогіці. Схарактеризовано особистісний чинник у соціально-педагогічній діяльності. At the present stage of development of Ukrainian society is relevant studies of innovative processes in social and pedagogical work, determining the regularity and principles of social pedagogy. The purpose of the article is the analysis of humanistic innovative processes in the social pedagogy, as humanist approach is most important in social and pedagogical activities. The article deals with the essence of the concepts of innovation, the innovation process. The regularity and principles of social and pedagogical work are analysed, and also the types of innovations in social pedagogy are defined. The Innovation is seen not only as a willingness to perception, production and application of new and primarily as openness. According to the personal factor of social and educational activities, it means: the openness the social teacher to dialogic interaction with pupils, which implies the equality of psychological positions of both sides; the openness to culture and society that turns out in pursuit of the social educator change reality, investigate the problems and choose the optimal ways of their solution; the openness of their «I», your own inner world, that is the organization of such pedagogical environment, which will contribute to the formation and development of the image «I». The social innovation can be defined as conscious organized innovations or new phenomenon in the practice of social and pedagogical work, which is formed at a certain stage of social development according to the social constantly changing conditions, and provides the effective positive changes in the social sphere. The sources of social innovation is primarily the social problems, the changing of society’s needs and the environment, that can’t be solved using the traditional methods. Further studies need the problems of training the future social pedagogues to innovation activities, as well as their practical willingness to apply the new socio and pedagogical technologies together with different age categories.
The Humanistic Orientation of Innovation Processes in Social Pedagogy
Keywords: нововведення; інноваційний процес; інноватика; педагогічна інноватика; соціально-педагогічна робота; novelty; innovation process; social and educational work; innovation, pedagogical innovation